The Implementation of Digital Ecosystem in English Education Context as Part of Institutional Strategy: A Case Study in UIN Syahada Padangsidimpuan - Hamka, Hamka; Najiah, Nurun (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2026)
The rapid development of digital technology has encouraged higher education institutions to adopt digital transformation strategies to improve institutional performance. However, studies on the role of integrated digital ecosystems in English education performance remained limited. This study aimed to examine how digital ecosystem development functions as an institutional strategy to enhance English education performance at UIN Syahada Padangsidimpuan. A qualitative case study design was employed. Data were collected through interviews, observations, and document analysis, and were analyzed thematically. The findings showed that digital ecosystem development served as an institutional strategy integrating learning processes, academic services, and institutional management. This ecosystem was built through the alignment of technological infrastructure, academic information systems, digital learning platforms, and human resource readiness. These components are interconnected and support institutional effectiveness. The study identified three key contributions to performance: improved learning quality, increased service efficiency, and strengthened data-driven management. This study provided a comprehensive understanding of ecosystem-based digital transformation and highlighted its role in enhancing English education performance.